L'histoire de Bone - Allison, Dorothy (Editions 10/18, 1999)
En Caroline du Sud, les étés sont étouffants. Les soirées se passent sur la véranda, à boire du thé glacé et à raconter des histoires. Ruth Anne Boatwright, surnommée Bone par sa famille et estampillée " bâtarde " par le comté de Greenville, se souvient. Elle revoit sa grand-mère édentée, impertinente, ses tantes farouches, usées par leurs grossesses, ses oncles violents, ivrognes pris au piège de leur misère. Elle se souvient de l'amour qu'elle portait à sa mère et de la haine grandissante qu'elle éprouvait pour son beau-père. Elle se souvient et elle raconte, avec une brutale sincérité, les aspirations d'une petite fille, la violence insoutenable, l'amour obstiné. Ce premier roman largement autobiographique, écrit pour exorciser cette enfance brûlée, a été finaliste pour le National Book Award en 1992
Keywords: 1900-1999; 1950-1959; amériques; approches et analyses; inceste; inégalités; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Pretty in punk: girls' gender resistance in a boys' subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
https://www.rutgersuniversitypress.org/pretty-in-punk/9780813526515/
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; culture populaire; entretien; ethnographie; genre; harcèlement sexuel; montréal; nouvelle-orléans; patriarcat; périodes historiques; régions géographiques; résistance; san francisco; stéréotypes de genre; systèmes d'oppressions; thématiques; violences

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (VLB, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Quand la violence parle du sexe : analyse du discours thérapeutique pour hommes violents - Letarte, Lise (Université du Québec à Montréal, 1998)
Keywords: IREF; amériques; discipline; hommes* violents; mémoires/thèses; québec; régions géographiques; sciences humaines; sexologie; thématiques; violences; violences contre les femmes*

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (Les éditions du remue-ménage, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Kanehsatake 270 ans de résistance (Office national du film du Canada, 1993)
"Par une chaude journée de juillet 1990, une confrontation historique a propulsé les problèmes des Autochtones de Kanehsatake et du village d'Oka au Québec au premier plan de la scène internationale et de la conscience des Canadiens. Au cours de cet été épuisant, la productrice et réalisatrice Alanis Obomsawin, elle-même Indienne abénaquise, a passé 78 jours et nuits angoissants derrière les barricades dressées par les Mohawks, à tourner des images du conflit armé les opposant à la Sûreté du Québec et l'Armée canadienne."–Conteneur.
Place: Montréal
Keywords: 1900-1999; 1990-1999; Kanehsatake; amériques; approches et analyses; canada; cinéma; communication; cours; discipline; féminisme autochtone; justice sociale; militance; oka; premier cycle; premières nations; périodes historiques; québec; régions géographiques; résistance; sex2283; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Queers read this - Anonyme (1990)
A leaflet distributed at pride march in NY. Published anonymously by Queers.
Keywords: LGBTQIA2+; VIH; amérique du nord; amériques; approches et analyses; hétérosexisme; identités LGBTQIA2+; militance; privilèges; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Carol - Highsmith, Patricia (Calmann-Lévy, 1990)
Elles se regardèrent au même instant. Thérèse avait levé les yeux de la boîte qu’elle était en train d’ouvrir et la femme venait de tourner la tête vers elle. Elle était grande et blonde, longue silhouette gracieuse dans un ample manteau de fourrure, qu’elle tenait entrouvert, la main posée sur la hanche. Ses yeux étaient gris, décolorés et pourtant lumineux comme le feu, et ceux de Thérèse, captifs, ne purent s’en détacher. Elle entendit la cliente qui lui faisait face répéter une question et elle resta muette. La femme la regardait, elle aussi, l’air préoccupé comme si une partie de son attention était fixée sur l’achat qu’elle s’apprêtait à faire et, bien qu’il y eût plusieurs vendeuses entre elles deux, Thérèse fut certaine qu’elle allait venir vers elle. Carol est le récit d’une obsession. Refusé à l’origine par son éditeur américain, ce roman a paru une première fois en France sous le titre Les Eaux dérobées signé du pseudonyme de Claire Morgan. Sa réédition permet de redécouvrir l’un des ouvrages les plus marquants du XXe siècle, injustement méconnu. Si le sujet ne fait aujourd’hui plus scandale, Carol conserve son odeur sulfureuse et figure parmi les oeuvres cultes de la littérature lesbienne. Patricia Highsmith y dévoile avec force et sensibilité un amour qui revendique sa liberté dans l’Amérique des années 50.
Keywords: 1900-1999; 1950-1959; amour; amériques; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; roman; régions géographiques; sexualité; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Queer Nation Manifesto - Queer Nation (Infokiosk, 1990)
Texte d’un manifeste initialement distribué par des personnes marchant aux côtés du contingent d’Act Up à la Gay Pride de New York, 1990.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; act up; amériques; approches et analyses; cours; gay pride; manifeste; militance; new york; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; violences; états-unis

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

Women, violence and social control - Hanmer, Jalna; Maynard, Mary (Humanities, 1987)
Keywords: amériques; continuum de violences; cours; discipline; europe; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; trs3500; violences; violences conjugales; violences contre les femmes*; états-unis

Des cailloux blancs pour les forêts obscures - Marchessault, Jovette (Leméac, 1987)
Qualifié à sa parution en 1987 de « roman du troisième œil » par Gloria F. Orenstein, ce livre raconte un moment dans la vie de Jeanne – depuis sa retraite des Appalaches, au sein d’une petite communauté d’esprits nouveaux –, alors que se meurt sa compagne, Noria. Aviatrice, cette dernière sauve des laboratoires les bêtes torturées à des fins de recherches expérimentales. Sur le seuil de sa vie revient son père, le Lion de Bangor, avec qui elle s’était réconciliée. Ce médecin, qui étudie les cellules souches du cancer, lève enfin pour Jeanne l’écrivaine les derniers voiles sur la vie de Noria : sa naissance, son enfance au sein du Ku Klux Klan, ce fils qu’elle a perdu, et cet amour infini que le Lion lui porte, un amour « comme ces ponts miraculeux sur lesquels nous avançons les uns vers les autres. » « Ce dernier volet de la trilogie Comme une enfant de la terre met en scène Noria, une aviatrice qui, telle une chamane, vole à travers le ciel nocturne de l’Amérique du Nord pour livrer au monde un message de salut et un espoir de guérison, et Jeanne, l’écrivaine qui pratique son propre art magique de la guérison : l’art de la littérature. » — GLORIA F. ORENSTEIN
Keywords: 1900-1999; amériques; approches et analyses; care; histoire et politique; hétérosexisme; littérature québécoise; périodes historiques; racisme; roman; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
https://www.persee.fr/doc/grif_0770-6081_1986_num_34_1_1698
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Female sexual slavery - Barry, Kathleen (New York University Press, 1984)
Keywords: amériques; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; fem9000; lit3220; premier cycle; prostitution; régions géographiques; sciences humaines; sociologie; thématiques; violences; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Articles presentés à la Scholar and the Feminist IX conference, tenue le 24 avril 1982 au Barnard College dans la ville de New York.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

La Mère des herbes - Marchessault, Jovette (Quinze, 1980)
Second volet d'une trilogie romanesque intitulée Comme une enfant de la terre. Le premier volet (Le crachat solaire) a obtenu le Prix France-Québec 1976. Imprécations et transgressions. Un roman "autobiographique et épique", violent, incantatoire, poétique, révolté. L'héroïne est une petite Québécoise élevée dans une culture de violence (mâle et chrétienne) et d'intimidation, qui raconte ses expériences et ses intuitions, les instants de bonheur passés avec sa grand-mère autochtone, pianiste et guérisseuse, etc.
Keywords: amériques; approches et analyses; autobiographie; enfance; littérature québécoise; patriarcat; québec; roman; régions géographiques; systèmes d'oppressions; thématiques; violences; écriture des femmes*

L'orientalisme : l'Orient créé par l'Occident - Said, Edward W. (Seuil, 1980)
D'Eschyle à Kissinger, de Marx à Barrès, l'Occident a tenu un discours sur l'Orient. Mais, puisque «l'Orient» n'existe pas, d'où vient ce discours et comment expliquer son étonnante stabilité à travers les âges et les idéologies? «L'Orient» est une création de l'Occident, son double, son contraire, l'incarnation de ses craintes et de son sentiment de supériorité tout à la fois, la chair d'un corps dont il ne voudrait être que l'esprit. À étudier l'orientalisme, présent en politique et en littérature, dans les récits de voyage et dans la science, on apprend donc peu de choses sur l'Orient, et beaucoup sur l'Occident. Le portrait que nous prétendons faire de l'Autre est, en réalité, tantôt une caricature, tantôt un complément de notre propre image. L'idéologie orientaliste s'est échappée depuis longtemps déjà du cabinet des savants pour précéder Napoléon dans sa conquête de l'Égypte ou suivre la guerre du Liban. C'est de ce discours qu'on trouvera ici la magistrale archéologie, augmentée de la préface que l'auteur rédigea en 2003 pour le vingt-cinquième anniversaire de la publication originale de l'ouvrage.
Keywords: amériques; approches et analyses; arts; com5170; cours; discipline; discours dominant; europe; fem1000; fem3400; féminisme décolonial; har4600; har4610; occident; orient; premier cycle; régions géographiques; systèmes d'oppressions; thématiques; violences; études littéraires

Les Services sociaux vs les lesbiennes et les gais du Québec : un dossier noir - Rassemblement national des lesbiennes et gais du Québec. (Le RNLGQ, 1979)
Keywords: 1900-1999; 1970-1979; amériques; corps; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; québec; régions géographiques; santé; thématiques; violences

Georgie - Jutras, Jeanne-d'Arc (Pleine Lune, 1978)
Georgie vit son enfance dans un quartier défavorisé du Montréal des années cinquante. Elle apprend au fil des ans le prix à payer pour vivre son lesbianisme dans un monde clos où les sermons religieux n’empêchent ni la misère ni la faim. Georgie a la tendresse et la violence de celles qui savent qu’il leur faudra tout arracher à la vie, que rien jamais ne leur sera donné. Elle avance et vit sans compromis.Georgie est écrit comme un coup de poing sur la table, avec l’éloquence cinglante des gens patients, quand ils en ont ras le bol.Gilles Cossette, Lettres québécoises.
Keywords: 1900-1999; 1950-1959; amériques; personnes lesbiennes; périodes historiques; québec; roman; régions géographiques; sexualité; thématiques; violences

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children–The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis